Self-propelled forage harvester sales analysis - Larson, Geremy (Kansas State University, 2015)
Self-propelled forage harvesters are used to make feed for livestock. Producers prefer forage made with these machines because they are able to deliver a feed value that enables improved productivity of their animals in terms of milk production for dairy animals and weight gain for beef animals. Self-propelled forage harvesters are able to make a variety of feed from different crops, including whole-plant corn silage, earlage, and haylage, among others. The self-propelled forage harvester is a complex and expensive piece of machinery for a producer to own. The self-propelled forage harvester market in the United States is a growing market, but small when compared to other equipment such as combines. In today’s environment, productivity is crucial to the success of the agricultural producer. Self-propelled forage harvesters are no exception. Growth of the self-propelled forage harvester market is reflected in increased unit sales, total horsepower sold, and average horsepower of the selfpropelled forage harvesters sold in the United States. This study looks at changes in the number and size of self-propelled forage harvesters being purchased and what factors might be driving those changes. This study found that the amount of milk produced, the type of customer purchasing the equipment, and the average price of milk a producer received explained 81.2% of the variation in the number of self-propelled forage harvesters sold from 2000-2014. Study results also show that the size of dairy operation, the type of customer purchasing the equipment, and the average price of milk explained 88% of the variability in total horsepower of self-propelled forage harvesters sold from 2000-2014. Finally, the size of dairy operation that a typical cow comes from, the type of customer purchasing the equipment, and the average price of corn were able to explain 98% of the variation of average horsepower of self-propelled forage harvesters over that same time period. The model and analysis will be shared with product planners from John Deere as they develop new machine specifications for self-propelled forage harvesters in the future.
Keywords: Forage harvesters; Horsepower; Silage